A SUCCESSFUL AMNIOTIC MEMBRANE TRANSPLANT FOR ACUTE CORNEAL THERMAL INJURY: A CASE REPORT - Dewi AAASN AAASN (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2020)
Introduction: Burns to the eyelids, conjunctiva, cornea, or sclera, whether from thermal energy or a chemical cause, are a true ophthalmic emergency. Typical of the injury may vary but requires immediate evaluation and treatment. Ideal treatments aim to maximize corneal re-epithelialization and minimize both adnexal structural abnormalities as well as corneal vascularization or conjunctivalization. Objective: The objective is to present interventional management in patients with acute corneal thermal injury. Case Presentation: A 18 years-old girl was consulted from Plastic Surgery Department with diagnosed with grade I combustion at the face and right hand. Patient complained about ocular pain and blurred vision after got drenched with hot water on the right eye. The visual acuity measured 6/30 pin hole 6/15 on right eye. Normal intra ocular pressure on both eyes. The examination of the right eye revealed redness, swelling, combustion and excoriation on eyelid; ciliary injection on the conjunctiva, 360 degree chemosis limbal. The cornea was hazy with necrotic tissue and fluorescein test was positive with erosion whole surface, iris details were visible and lens was clear. The patient was planned for amniotic membrane transplant. The visual acuity one day after surgery was 2/60 and the examination was found ciliary injection, subjconjunctival bleeding and sutured amniotic membrane with bandage contact lens on the cornea. One month after surgery, her visual acuity become 6/6 with very light scar on the periphery of the cornea. Conclusion: Acute corneal thermal injury is a common injury and potentially blind if not treated properly. Good visual prognosis can still be obtained with early diagnosis and appropriate treatment, making correct and definitive diagnosis are very important in daily clinical practices for general ophthalmologist.